Comparison of decomposition of biodegradable mulching films under variable soil microbial conditions - Kim, Sung Jae; Shim, Jun-Yeop; Park, Kyoung Min; Park, Dong il; Heo, Na Young; Hwang, Su Jin; Park, Sung Hoon; Chung, Hyeon Woo; Lee, Jae Myun; Chung, Hee Chun (Frontiers in Microbiology, 2025)
IntroductionBiodegradable mulching films (BDMs) are sustainable alternatives to polyethylene, but their degradation efficiency is strongly influenced by soil microbial composition. This study investigated the effects of Bacillus subtilis and Clostridium perfringens, two soil bacteria with distinct metabolic traits, on the decomposition of BDMs with different structures.MethodsThree biodegradable films (BDM1, BDM2, BDM3) and a polyethylene control were buried in soils containing native microbes, B. subtilis, or C. perfringens and incubated for 210 days. Degradation was evaluated by weight loss, soil pH, microbial viability, and scanning electron microscopy (SEM) of surface morphology.ResultsAll BDMs degraded significantly more than polyethylene. The monolayer BDM3 exhibited the greatest weight loss and surface damage. Soils inoculated with C. perfringens underwent strong acidification (final pH < 5.5), which accelerated degradation, especially in CaCO₃-containing films. Although C. perfringens viability declined over time, accumulated acids sustained film breakdown. By contrast, B. subtilis maintained higher soil populations, promoted gradual degradation, and preserved near-neutral pH, resulting in moderate weight loss.DiscussionThese findings demonstrate that soil pH modulation and microbial activity jointly determine BDM degradation. While C. perfringens enhanced film loss through acidification, its agricultural use may pose risks including excessive soil acidification and pathogenicity. B. subtilis provided safer but slower biodegradation. Among the tested films, monolayer BDM3 was most susceptible to breakdown, making it a promising candidate for field application. Careful management of microbial inoculants and soil pH will be essential to maximize BDM performance and environmental safety.